Jerzy Grotowski - Slowiak, James; Cuesta, Jairo (London : Routledge, 2007)
Biography and context - Grotowski's key writings - Grotowski as director - Practical exercises
Onderzoek KASK Professioneel (OFVP)
boek
Keywords: Grotowski, Jerzy